2009
DOI: 10.1093/intqhc/mzp025
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of adverse events in Swedish hospitals: a retrospective medical record review study

Abstract: ObjectivesTo estimate the incidence, nature and consequences of adverse events and preventable adverse events in Swedish hospitals.DesignA three-stage structured retrospective medical record review based on the use of 18 screening criteria.SettingTwenty-eight Swedish hospitals.PopulationA representative sample (n = 1967) of the 1.2 million Swedish hospital admissions between October 2003 and September 2004.Main Outcome MeasuresProportion of admissions with adverse events, the proportion of preventable adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
213
2
42

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(268 citation statements)
references
References 12 publications
11
213
2
42
Order By: Relevance
“…Numerous studies in different countries have been conducted using this approach in the last years. These studies revealed adverse event rates of 5-15% of all acute care hospital admissions [4][5][6][7][8] . Approximately 50% of events were deemed preventable [5] .…”
Section: Health Care As a Risk: The Magnitude Of The Safety Problemmentioning
confidence: 99%
“…Numerous studies in different countries have been conducted using this approach in the last years. These studies revealed adverse event rates of 5-15% of all acute care hospital admissions [4][5][6][7][8] . Approximately 50% of events were deemed preventable [5] .…”
Section: Health Care As a Risk: The Magnitude Of The Safety Problemmentioning
confidence: 99%
“…When adverse events are not controlled or prevented, they lead to long-term hospitalization, death, disability at discharge time, or changes in primary treatments (9,10). In developed countries, the incident ranges from 3.5% in the U.S. (11), 9.2% in Canada (12), to 12.3% in Sweden (13).…”
Section: Introductionmentioning
confidence: 99%
“…31 In stage 2, using the modular review form 2 (MRF2), doctors trained in the use of a standard set of questions analyse positively screened records in detail to determine whether or not they contain evidence of an AE. The basic method has been followed in all the major epidemiological studies, 14,16,[32][33][34][35][36][37][38][39] although there have been modifications to the review form and data capture methods. 30 Previous work in a UK setting, 16,24 assessing the sensitivity of the two-stage review process, reported a sensitivity of 92% and a specificity of 62%.…”
Section: Retrospective Case Note Reviewmentioning
confidence: 99%